Primary science for teaching assistants - Feasey, Rosemary (Routledge, 2007)
This book takes the reader, step by step, through issues and strategies relating to supporting the teacher and children in science lessons. Each chapter begins by setting out the key issues to be developed and finishes with a summary that reminds the reader of key points from the chapter.